EKSTRAKSI DAN KARAKTERISASI PEKTIN DARI LIMBAH KULIT JERUK (CITRUS SINENSIS (L.)) SEBAGAI MATERIAL POTENSIAL ADSORBEN - Rifa Fazira Rizki; Muhammad Reza (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2026)
Orange peel waste (Citrus sinensis (L.)) is a promising biomass source of pectin for functional materials. The purpose of the research is to extract and analyze pectin from orange peel waste as a potential adsorbent. This work uses an environmentally friendly acid hydrolysis extraction process to prepare adsorbent materials. The extraction was carried out for 45 minutes at 95 °C in a 10% citric acid solvent (pH 1.5). Organic acid was chosen to reduce the breakdown of pectin into pectic acid while simultaneously acting as a cross-linker. The results indicated a yield of 2.545% ± 0.035%. FTIR analysis verified the existence of particular pectin functional groups, including hydroxyl (O-H) vibrations at 3359.78 cm⁻¹, carbonyl (C=O) at 1713.11 cm⁻¹, and C-O ether at 1096.70 cm⁻¹, which is similar to commercial pectin. The abundance of active groups in pectin suggests that the extracted pectin has a great potential for synthesis into porous materials like hydrogels. These materials are designed to act as adsorbents for contaminants in water via physisorption and chemisorption mechanisms, providing green chemistry-based environmental management solutions.